filmov
tv
If y=(x^2-1)^n ,prove that (x^2-1)yn+2 +2xyn+1 - n(n+1)yn =0 Hence if Pn = d^n/dx^n {(1-x^2)dPn/dx..
![preview_player](https://i.ytimg.com/vi/K_vsUJLx_24/sddefault.jpg)
Показать описание
If y=(x^2-1)^n ,prove that (x^2-1)yn+2 +2xyn+1 - n(n+1)yn =0 Hence if Pn = d^n/dx^n {(1-x^2)dPn/dx} +n(n+1)Pn = 0
For pdf notes
Keywords
If y=(x^2-1)^n ,prove that (x^2-1)yn+2 +2xyn+1 - n(n+1)yn =0
If y=(x2-1)n ,prove that (x2-1)yn+2 +2xyn+1 - n(n+1)yn =0
If y=(x^2-1)n ,prove that (x^2-1)yn+2 +2xyn+1 - n(n+1)yn =0
If y=(x²-1)^n ,prove that (x²-1)yn+2 +2xyn+1 - n(n+1)yn =0
#bsc
#nkgc
successive differentiation
Thanks for watching 😊
NKG
For pdf notes
Keywords
If y=(x^2-1)^n ,prove that (x^2-1)yn+2 +2xyn+1 - n(n+1)yn =0
If y=(x2-1)n ,prove that (x2-1)yn+2 +2xyn+1 - n(n+1)yn =0
If y=(x^2-1)n ,prove that (x^2-1)yn+2 +2xyn+1 - n(n+1)yn =0
If y=(x²-1)^n ,prove that (x²-1)yn+2 +2xyn+1 - n(n+1)yn =0
#bsc
#nkgc
successive differentiation
Thanks for watching 😊
NKG
-
Nitin Kumar Gupta Classes
-
If y=(x^2-1)^n
-
prove that (x^2-1)yn 2 2xyn 1 - n(n 1)yn =0 If y=(x^2-1)n
-
prove that (x^2-1)yn 2 2xyn 1 - n(n 1)yn =0 If y=(x2-1)n
-
prove that (x2-1)yn 2 2xyn 1 - n(n 1)yn =0 if y=(x^2-1)^n
-
prove that (x^2-1)yn 2 2xyn 1 - n(n 1)yn =0 Successive differentiation Nitin Kumar Gupta Classes